Evaluation of the epidemiological profile of vaccination against the H1N1 virus in the state of Piauí, Brazil (Research, Society and Development, 2020)
The most recent H1N1 pandemic occurred in 2009 and Brazil was one of the countries affected by the H1N1 pandemic that year, totaling 46,355 cases. The end of this pandemic happened, especially, due to the vaccination campaigns that started to be carried out. Currently to ensure proper protection, the vaccine needs to be administered annually, however even in light of the vaccine's efficiency, annual deaths from H1N1 still occur, often because not all of the population has access to the vaccine.  Within this important context, the present study evaluated the epidemiological profile of vaccination against the H1N1 virus in the state of Piauí, addressing the vaccine coverage against the virus in the population of Piauí, verifying the existence of an immunization relationship against influenza and mortality from H1N1 in the population. The study consists of a documentary research with a quantitative and descriptive, transversal, retrospective approach, carried out from the SI-PNI database (Information System of the National Immunization Program) and TABNET (Health Information) through the Informatics Department of the Unified Health System (DataSus). The search criterion was defined as selecting the number of people who received the vaccine against the H1N1 virus, as well as the number of deaths in the time frame from 2017 to 2019 and the age of deaths. The results show that in the state of Piauí it reached levels close to the vaccine targets in two of the three years analyzed. Thus, a lower number of deaths was noted in the years that they reached rates close to the target set for vaccination coverage. The age group with the highest number of deaths comprises the elderly, which may be related to the low immunity and the presence of comorbidities that is common at this age. Thus, the study concluded that in the state of Piauí, immunization against H1N1 reduces the number of deaths from the virus, thus the research contributes to the planning of vaccine promotion measures adjusted to the most vulnerable groups, in order to further minimize the number of deaths, by H1N1.